Syntactic and Rhetorical Features of Medical Research Article Titles in National and International Journals - Taufik Akbar Azwar; Safnil Arsyad (Universitas Negeri Semarang, 2026)
Writing medical Research Articles (RA) titles in English is a challenging endeavor, particularly for those who come from an English as a Foreign Language (EFL) background. This study thus sought to provide insights into the titling practices of medical RAs in Indonesian national and international journals. It aimed to uncover syntactic structures and rhetorical combinations of medical RA titles. A comparative mixed-methods design was employed to examine 120 RA titles published between 2021 and 2024 from 4 different international medical journals and 4 different national medical journals. The results suggested that RAs published in international medical journals have longer titles than those in national medical journals. Compound phrase titles are the most dominant syntactic feature in international medical journals, while nominal phrase titles are the most common syntactic feature in national medical journals. The most frequent rhetorical combination is the topic–method category. Finally, the indicative-form titles are far more dominant than the interrogative-form titles. In essence, there are meaningful similarities and differences between RA titles published in international and national journals, which potentially could have implications for English for Medical Purposes. Finally, the findings contribute to informing the titling practices of medical RAs in two distinct groups of journals.